The End of the World: Apocalypse and its Aftermath in Western Culture - Lisboa, Maria Manuel (Open Book Publishers, 2011)
This book examines historical and imaginary scenarios of apocalypse, the depiction of its likely triggers, and imagined landscapes in the aftermath of global destruction. Its discussion moves effortlessly from classic novels including Aldous Huxleys Brave New World, George Orwells Nineteen Eighty-Four and Margaret Atwoods Oryx and Crake, to blockbuster films such as Blade Runner, Armageddon and The Terminator. The author also takes into account religious doctrine, scientific research and the visual arts to create a penetrating, multi-disciplinary study that provides profound insight into one of Western cultures darkest and most enduring preoccupations.
Directory of Open Access Books: DOAB.
Multi-User.
English.
Includes bibliographical references (p. [177]-186) and index.
Keywords: Apocalypse in literature; RELIGION / Christianity / Literature & the Arts; Multi-User.; Electronic books